Performance of solar parabolic dish thermoelectric generator with PCM. (2021) - Muthu, G.; Thulasi, S.; Dhinakaran, V.; Mothilal, T.
Abstract: In this work the results of experimental analysis of solar parabolic dish thermoelectric generator (TEG) are presented. The model of TEG was designed for the use of solar radiation as a heat source. The solar parabolic dish is fabricated by using polished aluminium sheet as concentrated surface. Thermoelectric generator consists of commercial thermoelectric module made of bismuth telluride (Bi2 Te3 ) embedded between the receiver plate and Phase change material (PCM) cooled heat sink which is place on the focal plane of manual solar tracking parabolic dish collector. PCM absorbs heat during its melting thus stabilizing temperature of cold side of TEG. The concentrated solar radiation and the PCM cooled heat sink is the driving potential to generate electricity, various operating parameter like receiver plate temperature, cold side temperature, mean temperature of PCM, power output and conversion efficiency with respect to wind velocity and solar radiation are studied.